New species and notes on Microveliinae from northern South America (Hemiptera: Heteroptera: Veliidae) - Aristizabal-Garcia, Hernan; Burguez Floriano, Carla Fernanda [UNESP]; Figueiredo Moreira, Felipe Ferraz; Bispo, Pitagoras Da Conceicao [UNESP] (Magnolia Press, 2015)
Euvelia mazzucconiae sp. nov., from northern Colombia is described, illustrated, and included in an updated identification key to the species of the genus. A map with the known geographical distribution of the species of Euvelia is presented. Additionally, two species from Colombia previously placed in the genus Paravelia are transferred to Microvelia and a species of the latter genus is synonymized, such that Paravelia acantha Padilla-Gil, 2013 = Microvelia acantha (Padilla-Gil, 2013) comb. nov., Paravelia fanera Padilla-Gil, 2013 = Microvelia fanera (Padilla-Gil, 2013) comb. nov., and Microvelia amrishi Makhan 2014 = Microvelia mimula White 1879 syn. nov.
Keywords: Aquatic insects; Neotropical Region; taxonomy; water striders